Doenças Neurológicas de Animais Domésticos nas Mesorregiões do Agreste e Mata Paraibana - Barbosa, Francisca Maria Sousa (2021)
The disorders that affect the central nervous system of domestic species are generally irreversible and considered as one of the main causes of death, consequently responsible for considerable economic losses in the agricultural sector. The objective of this study was to describe the nervous diseases that affect domestic species (cattle, sheep, goats, horses, pigs, dogs and cats) in the state of Paraíba. Evaluations of the necropsy and biopsy protocols were performed from August 2013 to December 2019 at the Veterinary Pathology Laboratory of the Federal University of Paraíba (LPV-UFPB) and 4,106 protocols were evaluated, of which 243 cases were diagnosed with nervous diseases. The diseases were classified into inflammatory and parasitic, toxic and toxic infections, neoplasms, degeneratives, developmental disorders, injuries caused by physical agents, other disorders and diseases of undetermined etiology, and a literature review of each nervous disease was performed. Then the diseases were grouped and added in decreasing order of the number of cases: infectious 103 (2.50%), toxic and toxic infections 41 (0.99%), injuries caused by physical agents 28 (0.68%), neoplasms 21 (0.51%), nutritional and metabolic disorders 20 (0.48%), other disorders 11 (0.26%), developmental disorders 10 (0.24%) and degenerative six (0.14%). Among these categories, the main diagnosed diseases were: infectious (distemper 23.50%, rabies 13.50%, bacterial or suppurative meningitis 8.73% and myeloencephalopathy by type 1 equine herpesvirus, 9.70%, equine encephalomyelitis 7, 76%); toxic and toxic infections (enterotoxemia 39.0%, tetanus 26.8%, edema disease 17.0%, botulism 7.3%); neoplasms (malignant tumor of the peripheral nerve sheath 61.9%, bovine leukosis 14.2%, pituitary carcinoma 9.5%); injuries caused by physical agents (traumatic brain injury 53.5%, trauma to the spinal cord 39.2%); nutritional and metabolic disorders (hepatic encephalopathy 20%, pregnancy toxemia 20%, gangliosidosis 20%, and uremic encephalopathy 15%, cervical scoliosis associated with copper deficiency 15%); degenerative (polioencephalomalacia 83.33%); developmental disorders (hydrocephalus 40%, bicephaly 20%, skull bifid and meningocele 20%); other disorders and diseases of undetermined etiology (post-anesthetic syndrome 52.8%, cholesteatoma 14.2%). The importance of infectious and parasitic diseases was evidenced, with a diagnosis of 2.50% (103/243) of the cases received. The importance of infectious and parasitic diseases was evidenced, with a diagnosis of 2.50% (103/243) of the cases received. Among the categories reviewed, the parasitic and infectious group stood out, with diseases such as distemper (23.5%/103), rabies (13.5%/103) and myeloencephalopathy by herpesvirus type 1 (9.7% / 103). It is concluded that neurological diseases represent an important cause of death or euthanasia in domestic species. Knowledge about the main diseases diagnosed in the state of Paraíba is of paramount importance for diagnosis in the field, this allows the veterinarian to know the possible differential diagnoses.